2011
DOI: 10.1007/s00213-011-2481-3
|View full text |Cite
|
Sign up to set email alerts
|

Memory improvements in elderly women following 16 weeks treatment with a combined multivitamin, mineral and herbal supplement

Abstract: Sixteen weeks ssupplementation with a combined multivitamin, mineral and herbal formula may benefit working memory in elderly women at risk of cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 67 publications
(81 reference statements)
1
100
1
Order By: Relevance
“…Furthermore, we demonstrated that the gamma-GCS activity, the first enzyme in the GSH biosynthesis, was upregulated in the prefrontal cortex of LDLr -/mice regardless of age, signaling an upregulation of GSH biosynthesis [84]. In this context, antioxidants have been shown to reverse learning and memory deficits observed in aging mice and in experimental models of Alzheimer's disease [85,86]. For instance, Farr et al [87] showed that natural antioxidants of extra virgin olive oil have beneficial effects on learning and memory deficits of SAMP8 mice (a model of agerelated learning/memory impairments) by reversing oxidative damage in the brain.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, we demonstrated that the gamma-GCS activity, the first enzyme in the GSH biosynthesis, was upregulated in the prefrontal cortex of LDLr -/mice regardless of age, signaling an upregulation of GSH biosynthesis [84]. In this context, antioxidants have been shown to reverse learning and memory deficits observed in aging mice and in experimental models of Alzheimer's disease [85,86]. For instance, Farr et al [87] showed that natural antioxidants of extra virgin olive oil have beneficial effects on learning and memory deficits of SAMP8 mice (a model of agerelated learning/memory impairments) by reversing oxidative damage in the brain.…”
Section: Discussionmentioning
confidence: 86%
“…The same treatment was associated with improvements in contextual recognition memory performance in men aged between 50 and 74 years who had a sedentary lifestyle [10]. Macpherson et al [26], also showed that 16-week supplementation with a SMV formula designed for older women (50+ Ultivite®) was associated with faster speed of spatial working memory performance.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis found evidence that supplementation with multivitamins reduces the odds of cognitive decline, potentially also linked to the development of Alzheimer's disease [ 36 ] . Multivitamins were reported to slow down the progression of cognitive decline in elderly women [ 37 ] . Moreover, increased intakes of vitamins were also linked to alertness, general well-being and a reduction in negative mood-swings in elderly men [ 38 ] .…”
Section: Micronutrients and Cognitive Functionsmentioning
confidence: 99%